Determinan Market Share Perbankan Syariah di Indonesia - Eliana, Eliana; Zarman, Nazri; Ismuadi, Ismuadi; Astuti, Intan Novia; Ayumiati, Ayumiati (Esensi: Jurnal Bisnis dan Manajemen, 2020)
Sharia banking is currently very popular with the Indonesian people, so to prepare for this increasingly selective business competition, Islamic Commercial Banks are required to improve their company performance so that investors are attracted to invest. This study aims to determine the effect of BOPO, ROA, NPF, and DPK on the market share of Islamic banking in Indonesia. The samples used were BUS and UUS with 52 data. Multiple linear regression is used as an analysis technique to produce a detailed description of the relationship of each variable used. The regression results tell that BOPO and DPK have no significant effect on market share, while ROA and NPF have a positive and significant effect on market share in Islamic banking in Indonesia.